Optoelectronic Materials, Devices, and Applications - Niu, Pingjuan; Pei, Li; Mei, Yunhui; Bai, Hua; Shi, Jia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In total, ten papers are included in this reprint. New advances in optoelectronic materials have been reported for crystals, electrodes, and bonding materials. Zakrzewski et al. analyzed photothermal piezoelectric spectroscopy of Cd1−xBexTe, showing potential in X-ray and γ-ray detectors. Han et al. investigated characteristics of a copper foil three-electrode planar spark gap high-voltage switch integrated with EFI. Ding et al. showed a way to improve electrochemical migration resistance of nanosilver paste as a bonding material. New advances have been reported for LEDs and photonic crystal waveguides. Bai et al. proposed a new method for the measurement of adhesive force between a single μLED and the substrate. Zhang et al. analyzed strain relaxation effect on the peak wavelength of blue micro-LEDs. Shi et al. proposed an all-dielectric terahertz photonic crystal waveguide operating in 6G terahertz communication window. New applications of optoelectronic materials and devices have also been reported for piezoelectric sensors, crystal materials, SAR, and OCT. Wang et al. established a collision model of wheat grains impacting a force plate with a piezoelectric sensor. He et al. demonstrated application of a BaGa4Se7 crystal in a tunable and compact mid-infrared optical parametric oscillator with a repetition rate of up to 250 Hz. Wang et al. proposed a new feature learning method for the automatic target recognition of SAR images. Shi et al. reviewed the quantitative assessment methods used for early enamel caries with OCT.